2021
DOI: 10.5294/aqui.2021.21.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the organizational culture for patient safety in the hospital setting: A systematic review

Abstract: Objective: To identify the effect of the organizational culture on patient safety in the hospital context. Materials and methods: A systematic review, without meta-analysis, registered in PROSPERO with number CRD42020162981. Cross-sectional and observational studies were selected that assessed the safety environment and safety culture published between 2014 and 2020 in journals indexed in the EMBASE, Latin American and Caribbean Literature in Health Sciences (Literatura Latinoamericana e do Caribe em Ciências… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(142 reference statements)
0
1
0
1
Order By: Relevance
“…Estudos como esta revisão tornam-se instrumento valioso para explorar o contexto do clima de segurança, compreender a aplicação da ferramenta SAQ em diferentes contextos. A discussão de estratégias para o aprimoramento do cuidado deve ser realizada de forma constante buscando melhor dimensionamento e recrutamento de pessoas, recursos humanos, valorização dos profissionais, comunicação e cooperação entre as áreas e seus gestores, bem como o desenvolvimento de políticas públicas [49][50][51][52][53][54][55] .…”
Section: Discussionunclassified
“…Estudos como esta revisão tornam-se instrumento valioso para explorar o contexto do clima de segurança, compreender a aplicação da ferramenta SAQ em diferentes contextos. A discussão de estratégias para o aprimoramento do cuidado deve ser realizada de forma constante buscando melhor dimensionamento e recrutamento de pessoas, recursos humanos, valorização dos profissionais, comunicação e cooperação entre as áreas e seus gestores, bem como o desenvolvimento de políticas públicas [49][50][51][52][53][54][55] .…”
Section: Discussionunclassified
“…For instance, a systematic review by da Silva et al indicated that organizations with a healthy safety culture had lower rates of adverse events and better patient outcomes. 32 This underscores the importance of promoting and maintaining a strong patient safety culture within healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%